2020
DOI: 10.1002/pd.5734
|View full text |Cite
|
Sign up to set email alerts
|

Management of monochorionic twins discordant for structural fetal anomalies

Abstract: Objective: To review the perinatal management and outcomes of monochorionic twin pregnancies (MC) discordant for congenital anomalies (DCA). Methods: Retrospective, study of all MC DCA cases referred to our tertiary referral center from 1997 to 2018. We excluded cases complicated with twin-to-twin transfusion syndrome, twin anemia-polycythemia sequence, twin reversed arterial perfusion sequence or selective intra-uterine growth restriction. Patients were counseled about the possibility of expectant (EM) or int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Discordant structural anomalies are found in 3% [ 4 ] of MCDA pregnancies and with increasing use of next-generation genetic testing, more cases with genomic discordances are also likely to be found [ 5 ], perhaps further increasing the indications for selective fetal termination where appropriate. Although the fetal reduction in MCDA twins is well described, all techniques risk miscarriage or prematurity when performed in the pre-viable or pre-term period, with co-twin death occurring in 10-15% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discordant structural anomalies are found in 3% [ 4 ] of MCDA pregnancies and with increasing use of next-generation genetic testing, more cases with genomic discordances are also likely to be found [ 5 ], perhaps further increasing the indications for selective fetal termination where appropriate. Although the fetal reduction in MCDA twins is well described, all techniques risk miscarriage or prematurity when performed in the pre-viable or pre-term period, with co-twin death occurring in 10-15% [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Selective reduction carries the risk of complications including miscarriage or preterm delivery, depending upon the gestation at which this is performed and although latency to delivery is overall good there are still risks of significant prematurity and pregnancy loss. Most series describe cases being undertaken at 30 weeks of gestation or less with very few reported cases beyond this [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…sFGR was defined as a growth restriction in one fetus with an estimated fetal weight <10th centile and intertwin estimated fetal weight discordance of ≥25%, and was categorized according to Gratacos 16 . Discordant congenital anomalies include malformations of the circulatory system, nervous system, respiratory system, digestive system, urinary system, musculoskeletal system, and face and neck observed on ultrasound examination 17 . TAPS was defined as discordant middle cerebral artery peak systolic velocity (MCA‐PSV) (>1.5 multiples of the median (MoM) in donors and <1.0 in recipients) without signs of oligo‐ and polyhydramnios and was classified into stage I‐V 18 .…”
Section: Methodsmentioning
confidence: 99%
“…-1029 digestive system, urinary system, musculoskeletal system, and face and neck observed on ultrasound examination. 17 TAPS was defined as discordant middle cerebral artery peak systolic velocity (MCA-PSV) (>1.5 multiples of the median (MoM) in donors and <1.0 in recipients) without signs of oligo-and polyhydramnios and was classified into stage I-V. 18 In 2018, delta MCA-PSV >0.5 MoM was implemented as a new diagnostic criterion for TAPS. 19…”
Section: Indications For Selective Fetal Reductionmentioning
confidence: 99%
“…However, this may be technically challenging to perform in MC twins due to an increased thickness of the umbilical cord, therefore, some clinicians may prefer to perform these procedures in the second trimester due to technical feasibility, with a reported co-twin survival rate of 83% 79 . A recent cohort study evaluated the outcomes of the healthy co-twins in groups of discordant MC twins undergoing expectant management versus selective fetocide, and found that no significant differences in livebirth rates were seen with either form of management (88.5% expectant management, 82.7% selective fetocide, p=0.87) 83 . Therefore, the management of discordant anomalies remain controversial, and requires careful counselling and treatment planning with consideration of patient wishes.…”
Section: Controversies In the Management Of Discordant Anomaliesmentioning
confidence: 99%